The virtues and vices of speech - Pontano, Giovanni Gioviano, 1429-1503 (The I Tatti Renaissance library, 2019)
Although Pontano did not polish De sermone completely or provide books 2-6 with prefaces, as Summonte indicates in his own preface ("Appendix One"), he had substantially completed it about a year before his death. Although most appreciated as a collection of witticisms, De sermone is first and foremost a treatise of Aristotelian moral philosophy about the virtues and vices of speech. In 1.4.3 Pontano presents the treatise as a continuation of his other studies of the moral virtues and insists upon the concept that guides him, the Aristotelian doctrine that every moral virtue is a mean between two extremes, an excess and a deficiency, both of which are vices. De sermone provides an inventory of the kinds of speech in social situations, and Aristotle is Pontano's guide throughout. At one point he explains his method as exploring at greater length and a bit more searchingly subjects treated by Aristotle. Chapter 2.6 and sections 2.7.1-4 are a detailed summary of Aristotle's discussion of the mean of veracity and its extremes of ostentation and self-deprecation. Although Pontano does not say so, chapter 1.26 borrows heavily from Aristotle's discussion of the unnamed mean most resembling friendship and its extremes of contentiousness and obsequiousness.--